Comprehensive Physiology 2016
DOI: 10.1002/cphy.c150046
|View full text |Cite
|
Sign up to set email alerts
|

Neurocardiology: Structure‐Based Function

Abstract: Cardiac control is mediated via a series of reflex control networks involving somata in the (i) intrinsic cardiac ganglia (heart), (ii) intrathoracic extracardiac ganglia (stellate, middle cervical), (iii) superior cervical ganglia, (iv) spinal cord, (v) brainstem, and (vi) higher centers. Each of these processing centers contains afferent, efferent, and local circuit neurons, which interact locally and in an interdependent fashion with the other levels to coordinate regional cardiac electrical and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
109
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 226 publications
2
109
0
2
Order By: Relevance
“…Autonomic neuronal dysfunction plays a crucial role in the genesis of cardiac arrhythmias and/or progression of the failing heart (Fukuda et al, 2015; Vaseghi et al, 2008). The cardiac neuronal hierarchy is primarily focused on dynamic coordination of cardiac function to match whole body metabolic demands (Armour et al, 2004a) and includes neural networks located from the level of the heart (Ardell, 1994; Armour, 1991) and intra-thoracic extra-cardiac ganglia to the insular cortex (Oppenheimer et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic neuronal dysfunction plays a crucial role in the genesis of cardiac arrhythmias and/or progression of the failing heart (Fukuda et al, 2015; Vaseghi et al, 2008). The cardiac neuronal hierarchy is primarily focused on dynamic coordination of cardiac function to match whole body metabolic demands (Armour et al, 2004a) and includes neural networks located from the level of the heart (Ardell, 1994; Armour, 1991) and intra-thoracic extra-cardiac ganglia to the insular cortex (Oppenheimer et al, 1994). …”
Section: Introductionmentioning
confidence: 99%
“…At the organ level, the intrinsic cardiac nervous system (ICNS) comprises a distributed network of ganglia and interconnecting nerves (Ardell, 1994; Armour, 1991). Neurons within cardiac GPs interact in concert with neurons in intra-thoracic extra-cardiac (sympathetic) ganglia, nodose and dorsal root ganglia (DRG), and higher center neurons (including spinal neurons).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been shown that the ICNS has the capability to exert bidirectional integrated reflex control of cardiac electrical and mechanical function, even when functioning disconnected from all higher neural elements of the cardiac nervous system ([9] and [10]). Furthermore, intrathoracic reflex control of the heart is partially maintained following decentralization of stellate ganglia bilaterally [11]. In other words, the ICNS and ITNS are capable of a degree of autonomous function with respect to central inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Among these ganglia, common shared inputs (afferent and efferent), inter- and intra-ganglionic interconnections mediated by LCN’s sub-serve and assure beat-by-beat coordination of regional cardiac (electrical and mechanical) indices ([11] and [12]). Both the intrinsic and intrathoracic nervous systems receive central inputs and afferent inputs that represent a complex mix of information from the heart, lungs, carotid and aortic baroreceptors, viscera, periphery and a host of other factors.…”
Section: Introductionmentioning
confidence: 99%
“…GPs are not simply “relay stations” for ANS projections to the heart; they contain sympathetic efferent, parasympathetic efferent, sensory afferent, and local circuit neurons (8,9). Extensive processing of these inputs occurs at the level of the ICN.…”
mentioning
confidence: 99%